2018
DOI: 10.1002/ange.201806097
|View full text |Cite
|
Sign up to set email alerts
|

Formazanate Complexes of Hypervalent Group 14 Elements as Precursors to Electronically Stabilized Radicals

Abstract: The stability of molecular radicals containing main‐group elements usually hinges on the presence of bulky substituents that shield the reactive radical center. We describe a family of Group 14 formazanate complexes whose chemical reduction allows access to radicals that are stabilized instead by geometric and electron‐delocalization effects, specifically by the square‐pyramidal coordination geometry adopted by the Group 14 atom (Si, Ge, Sn) within the framework of the heteroatom‐rich formazanate ligands. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…7 Very recently, Gilroy and co-workers have reported hypervalent Ge(IV) radical anion (V) supported by formazanate ligand. 8 To the best of our knowledge, no acyclic neutral Ge(I) radical has been reported so far.…”
mentioning
confidence: 85%
“…7 Very recently, Gilroy and co-workers have reported hypervalent Ge(IV) radical anion (V) supported by formazanate ligand. 8 To the best of our knowledge, no acyclic neutral Ge(I) radical has been reported so far.…”
mentioning
confidence: 85%
“…Previous reports and our work , showed that π–π and p−π conjugation interactions could contribute to delocalize the energy density of the unpaired electrons and the steric effect could restrict intermolecular electron self-exchange behavior. On the basis of this idea, rigid aromatic rings (such as formazanate complexes, trioxotriangulene, and triphenylmethane) were often used as blocks to provide conjugation structure and steric effect to tune the stability of the radical intermediates. However, this simple introduction of the inactive aromatic units unavoidably results in reduction of specific capacities of the electrode materials.…”
Section: Introductionmentioning
confidence: 99%
“…21−23 Formazanate complexes of group 14 elements and ruthenium highlight the redox noninnocence of some classes of formazanate complexes. 15,24 Furthermore, boron chelates of formazanates not only exhibit tunable redox properties but are also in many cases photoluminescent, 25−30 finding applications as cell-imaging agents, 27,31 electrochemiluminescence emitters, 12,32,33 multifunctional polymers, 34,35 and precursors to a wide range of BN heterocycles. 36,37 In spite of these numerous examples, coordination complexes of formazans with third-row transition metals remain rare.…”
Section: ■ Introductionmentioning
confidence: 99%